PTH-127 Nutritional Status After Intestinal And Multivisceral Transplant. (9th June 2014) - Sharkey, L; Kratzing, C; Rutter, C; Gao, R; Butler, A; Woodward, J; Middleton, S
Abstract : Introduction: There is limited data on nutritional outcomes post intestinal transplantation in adults. This cohort of patients will inevitably be at high nutritional risk and undergoing major surgery is anticipated to have a further deleterious effect. Methods: Pre and post transplant anthropometric data and nutritional status of all patients undergoing intestinal or multivisceral transplantation from 2007 to 2013 who survived more than 30 days post transplant was collected prospectively. A dynamometer was used to assess grip strength in the non-dominant hand. Bone density was measured by dual x-ray absorptiometry (DEXA). Results: 42 patients have undergone transplant during the time period, full data is reported for 28 patients (Exclusions: 6 transplanted <3 months, 1 graft enterectomy, 4 died within 30 days of surgery, 3 no data). 15 patients received a Multivisceral transplant, 7 Modified Multivisceral and 6 Intestine only. Patients have been followed up for a median of 26 months, to December 2013 or death (n = 5). The mean BMI of patients at the time of assessment was 21.7 (Standard Deviation (SD) 3.5). Post-transplant, parenteral nutrition (PN) was given for a median of 24 days (range 2–134), enteral nutrition (EN) was given for a median of 57.5 days (range 0–262). The mean maximum weight loss post transplant was 16.6% of pre-transplant weight (SD 7.65%). Over one third of patients lost 20% or more of their pre-transplant weight and only 5 patients have returned to or exceeded their previous weight, though all but one patient has gained weight from their nadir weight. Mean BMI at latest follow-up in survivors is 20.64 (SD 4.6). The majority of patients (20/23 survivors, 87%) are maintained on an oral diet. 2 patients (8.7%) with an intact graft require PN and 1 patient (4.3%) requires parenteral fluids. One patient (4.3%) continues on EN. Handgrip strength was measured pre and post transplant (median 17 months post, range 7–34) in 13 patients, 7 demonstrated an improvement, 2 were stable (<5% change) and 4 had worsened. 4/5 patients who were receiving long term PN pre-transplant and had serial DEXA scans showed significant improvements in bone density post transplant. Conclusion: The majority of patients post intestinal and multivisceral transplant have nutritional autonomy; only a small number require parenteral or enteral nutritional support. Improvements in bone density and muscle strength can be demonstrated post transplant. However, significant weight loss does occur in the post-operative period; this should be taken into consideration when patients are being listed and every attempt made to optimise pre transplant. Disclosure of Interest: None Declared.